Role of EZH2-mediated epigenetic modification on vascular smooth muscle in cardiovascular diseases: A mini-review - Luo, Haiyan; Li, Yao; Song, Honghu; Zhao, Kui; Li, Wenlin; Hong, Hailan; Wang, Yun-Ting; Qi, Luming; Zhang, Yang (Frontiers in Pharmacology, 2024)
Vascular smooth muscle cells (VSMCs) are integral to the pathophysiology of cardiovascular diseases (CVDs). Enhancer of zeste homolog 2 (EZH2), a histone methyltransferase, plays a crucial role in epigenetic regulation of VSMCs gene expression. Emerging researches suggest that EZH2 has a dual role in VSMCs, contingent on the pathological context of specific CVDs. This mini-review synthesizes the current knowledge on the mechanisms by which EZH2 regulates VSMC proliferation, migration and survival in the context of CVDs. The goal is to underscore the potential of EZH2 as a therapeutic target for CVDs treatment.Modulating EZH2 and its associated epigenetic pathways in VSMCs could potentially ameliorate vascular remodeling, a key factor in the progression of many CVDs.Despite the promising outlook, further investigation is warranted to elucidate the epigenetic mechanisms mediated by EZH2 in VSMCs, which may pave the way for novel epigenetic therapies for conditions such as atherosclerosis and hypertension.